Blood signatures for second stage human African trypanosomiasis: a transcriptomic approach - Mulindwa, Julius; Matovu, Enock; Enyaru, John; Clayton, Christine (BMC medical genomics, 2020)
Rhodesiense sleeping sickness is caused by infection with T. b rhodesiense parasites resulting in an acute disease that is fatal if not treated in time. The aim of this study was to understand the global impact of active T. b rhodesiense infection on the patient’s immune response in the early and late stages of the disease.